Impact of Various Effects of Smoking in the Mouth on Motivating Dental Patients to Quit Smoking - Hanioka, Takashi; Tsutsui, Akihito; Yamamoto, Mito; Haresaku, Satoru; Shimada, Kaoru; Watanabe, Takeshi; Matsuo, Tadayuki; Ojima, Miki (International Journal of Statistics in Medical Research, 2013)
We explored the impact of addressing personally relevant effects of smoking in the mouth on promoting the motivation to quit in a dental setting at personal and public levels. Stages of behavior change and attempts to quit smoking by smokers were recorded during dental visits. Dentists selected and gave motivational information from 24 topics relevant to a patient’s oral health status, risk, or dental treatment. During the dental visit, each topic was presented to patients. Topics of gingival melanin pigmentation and periodontal disease risk were most frequently presented. Progression through stages of behavior change and attempts to quit smoking were observed after presentation of each topic. At a personal level, progression through stages was most frequently observed after the patient was shown an image of pediatric dental caries and smoker’s palate, and attempts to quit was most frequently observed after the patient shown an image of the effects of smoking cessation and pediatric dental caries. At the public level, enhancing the motivation to progress through stages and attempts to quit was most frequently observed after the presentation of effects of smoking cessation and discoloration of teeth, although the intensity of enhanced motivation significantly correlated with the frequency of presentation, which was not the highest for these topics. Although various smoking effects on the mouth have potential impact on promoting the motivation to quit, the impact on enhancing motivation is not necessarily consistent at personal and public levels.